2019
DOI: 10.1177/1074248419883591
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone and Its Active Metabolite Prednisolone Attenuate Lipid Accumulation in Macrophages

Abstract: Background: Synthetic forms of glucocorticoids (GCs; eg, prednisone, prednisolone) are anti-inflammatory drugs that are widely used in clinical practice. The role of GCs in cardiovascular diseases, including atherosclerosis, is highly controversial, and their impact on macrophage foam cell formation is still unknown. We investigated the effects of prednisone and prednisolone on macrophage oxidative stress and lipid metabolism. Methods and Results: C57BL/6 mice were intraperitoneally injected with prednisone or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In order to elicit the anti-inflammatory properties, the synthetic glucocorticoids prednisone and prednisolone were administered to mice. The glucocorticoid-treated mice showed reduced triglyceride and cholesterol accumulation [ 97 ]. This finding supports the protective role of glucocorticoids in the inflammatory process of foam cell formation, and ultimately in the development of atherosclerosis [ 97 , 98 ].…”
Section: Macrophages and Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to elicit the anti-inflammatory properties, the synthetic glucocorticoids prednisone and prednisolone were administered to mice. The glucocorticoid-treated mice showed reduced triglyceride and cholesterol accumulation [ 97 ]. This finding supports the protective role of glucocorticoids in the inflammatory process of foam cell formation, and ultimately in the development of atherosclerosis [ 97 , 98 ].…”
Section: Macrophages and Atherosclerosismentioning
confidence: 99%
“…The glucocorticoid-treated mice showed reduced triglyceride and cholesterol accumulation [ 97 ]. This finding supports the protective role of glucocorticoids in the inflammatory process of foam cell formation, and ultimately in the development of atherosclerosis [ 97 , 98 ]. Another known regulator of inflammation is ApoA-I, which counteracts the inflammatory response through binding to ABCA1 to export cholesterol out of macrophages.…”
Section: Macrophages and Atherosclerosismentioning
confidence: 99%
“…18,19 In contrast, Jeries et al discovered that glucocorticoids presented antiatherogenic effect by protecting macrophages from lipid accumulation and foam cell formation. 20 After comprehensive consideration, the patient in this case receiving longterm low-dose prednisone and immunosuppressant and had no recurrence of vascular events during the 2-year follow-up. Therefore, we tend to think the macrovascular stenosis may be more related to SSc instead of prednisone.…”
Section: Discussionmentioning
confidence: 82%
“…Recent studies demonstrated glucocorticoid was associated with a dose‐dependent increase in risk of cardiovascular events, even low‐dose glucocorticoid increases the risk of cardiovascular disease 18,19 . In contrast, Jeries et al discovered that glucocorticoids presented antiatherogenic effect by protecting macrophages from lipid accumulation and foam cell formation 20 . After comprehensive consideration, the patient in this case receiving long‐term low‐dose prednisone and immunosuppressant and had no recurrence of vascular events during the 2‐year follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests long-term glucocorticoid exposure over the course of atheroma development can be athero-protective by reducing monocyte/macrophage recruitment and foam cell formation. Indeed, this is supported by a recent study demonstrating the direct ability of prednisone/prednisolone to reduce cholesterol accumulation in macrophages [65].…”
Section: Are Glucocorticoids Athero-protective or Drivers Of Lesion Development?mentioning
confidence: 74%